The implementation of interactive wordwall media as a strategy to enhance Student engagement in civics education at elementary school - Kurnialillah, Avia; Nafi’ah, Jamilatun (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2025)
The rapid development of technology in Indonesia presents new challenges in the field of education, particularly in increasing student engagement in every subject, including Pancasila Education. Based on observations and interviews conducted at SD Assunniyyah, it was found that students were less active in Pancasila Education classes, tending to be passive, bored, and rarely involved in question-and-answer sessions or discussions. The purpose of this study is to examine the implementation of the interactive Wordwall media as a strategy to enhance student engagement in Pancasila Education learning at the elementary school level. This research uses a qualitative method with a case study approach. The results show that the use of Wordwall media significantly increases student engagement in Pancasila Education, encouraging quicker responses, a greater willingness to ask questions, and creating a more enjoyable learning atmosphere. The implementation of interactive Wordwall media as a strategy to enhance student engagement in Pancasila Education at the elementary level has a significant long-term impact on the education sector. This media not only increases students’ active participation in the learning process but also fosters a positive attitude toward Pancasila Education, particularly in understanding the values of nationalism and character.